2007
DOI: 10.1007/s11427-007-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

The breeding of two polyploid rice lines with the characteristic of polyploid meiosis stability

Abstract: Polyploidization is a basic feature of plant evolution. Nearly all of the main food, cotton and oil crops are polyploid. When ploidy levels increase, yields double; this phenomenon suggested a new strategy of rice breeding that utilizes wide crosses and polyploidization dual advantages to breed super rice. Because low seed set rates in polyploid rice usually makes it difficult to breed, the selection of Ph-liked gene lines was emphasized. After progenies of indica-japonica were identified and selected, two pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 12 publications
0
51
0
2
Order By: Relevance
“…Meiosis of most polyploid rice triggered by genome duplication was unorganized, leading to low frequency normal pollen; consequently, most lines of polyploid rice had a seed set rate of under 40% and low yields. In our research, polyploid hybrid rice with a PMeS parent background showed stable meiosis and had a high seed set rate (Cai et al 2007). The discovery and application of PMeS in disrupting the low seed set rate would have great potential in contributing to research in polyploid rice in the future.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Meiosis of most polyploid rice triggered by genome duplication was unorganized, leading to low frequency normal pollen; consequently, most lines of polyploid rice had a seed set rate of under 40% and low yields. In our research, polyploid hybrid rice with a PMeS parent background showed stable meiosis and had a high seed set rate (Cai et al 2007). The discovery and application of PMeS in disrupting the low seed set rate would have great potential in contributing to research in polyploid rice in the future.…”
Section: Introductionmentioning
confidence: 61%
“…japonica lines Balilla-2X (commonly used in Japan), Balilla-4X, HN2026-2X, and HN2026-4X were used in this research. HN2026-4X, which has a high seed set rate, was considered a stable polyploid meiosis rice line (Cai et al 2004a(Cai et al , 2007. The Balilla-4X line without the PMeS background had a low seed set rate with disorganized meiosis behavior, and was applied as CK.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivated rice Sg99012 (O. sativa, AA, 2n = 2X = 24) is a japonica rice line stored at the Polyploid Genetics Lab of Hubei University, Wuhan, China. Sg99012-4X (AAAA, 2n = 4X = 48) is a high seed set tetraploid rice line with a polyploid meiosis stability (PMeS) gene selected by Cai et al (2007).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Polyploidy provides the benefits for plants such as heterosis (hybrid vigor) and gene redundancy which thus cause polyploids to be more vigorous and tolerant than their diploid progenitors. For instance, autotetraploid rice lines pMeS-1 and pMeS-2 (Polyploid Meiosis Stability) were produced and selected to improve the crop yields based on meiotic stability and high fertility (Cai et al 2007). However, little is known about effects of polyploidy on specific meiotic mutations after polyploidization in plants.…”
Section: Polyploidization Can Alleviate Disruptive Consequences In Somentioning
confidence: 99%